PROTOCOL: Gender‐Responsive Macro‐Level Policies and Women's Economic Empowerment in Sub‐Saharan Africa: An Evidence and Gap Map - David Sarfo Ameyaw; Takyiwaa Manuh; Sheila Agyemang Oppong; Clarice Panyin Nyan (Campbell Systematic Reviews)
ABSTRACT This Evidence and Gap Map (EGM) protocol aims to identify, map, and provide an overview of the existing evidence and gaps on gender‐responsive macro‐level policies and women's economic empowerment in sub‐Saharan Africa. Specifically, the EGM will: (1) identify which evidence clusters present opportunities for evidence synthesis and (2) identify the evidence gaps that require additional studies, research, and evaluations.